2016
DOI: 10.1105/tpc.15.01056
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Related Sequences Trigger Systemic mRNA Transport in Plants

Abstract: In plants, protein-coding mRNAs can move via the phloem vasculature to distant tissues, where they may act as non-cellautonomous signals. Emerging work has identified many phloem-mobile mRNAs, but little is known regarding RNA motifs triggering mobility, the extent of mRNA transport, and the potential of transported mRNAs to be translated into functional proteins after transport. To address these aspects, we produced reporter transcripts harboring tRNA-like structures (TLSs) that were found to be enriched in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
177
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(199 citation statements)
references
References 43 publications
6
177
1
Order By: Relevance
“…3 and 4 important intercellular cytoplasmic connecting channels for exchange of various macro-314 and micro-molecules (Turnbull and Lopez-Cobollo, 2013). The selective targeting of 315 mobile mRNA to PD (Figure 3 and 4) further supports that the trafficking of mobile 316 mRNA is triggered by specific RNA sequences rather than transcript abundance (Huang 317 and Yu, 2009;Zhang et al, 2016). The differential targeting of mobile and non-mobile 318 mRNAs may be a determining step for RNA movement.…”
Section: Discussion 278mentioning
confidence: 69%
See 2 more Smart Citations
“…3 and 4 important intercellular cytoplasmic connecting channels for exchange of various macro-314 and micro-molecules (Turnbull and Lopez-Cobollo, 2013). The selective targeting of 315 mobile mRNA to PD (Figure 3 and 4) further supports that the trafficking of mobile 316 mRNA is triggered by specific RNA sequences rather than transcript abundance (Huang 317 and Yu, 2009;Zhang et al, 2016). The differential targeting of mobile and non-mobile 318 mRNAs may be a determining step for RNA movement.…”
Section: Discussion 278mentioning
confidence: 69%
“…In addition, 73 recent evidence indicates that the transfer RNA (tRNA)-like structure on a subset of 74 mobile mRNAs is a signal triggering mRNA movement (Zhang et al, 2016). Thus, how 75 mobile mRNA is translocated cell-to-cell remains to be elucidated.…”
Section: A Mobile Ga-insensitive (Gai) or Flowering Locus T (Ft) Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we conclude that the presence of a tRNA coding sequence in the host protein-coding genes does not interfere with gene splicing. Interestingly, Zhang and coworkers [38] revealed an additional role of tRNA sequences in systemic mRNA transport in plants. These authors found that mobile mRNAs in Arabidopsis are enriched in tRNA-like motifs or are transcribed from genes located in close proximity to annotated tRNA loci, which form di-cistronic mRNA-tRNA transcripts at a high frequency (according to paired-end RNA-seq data).…”
Section: Discussionmentioning
confidence: 99%
“…To test the role of TLSs in the mobility of plant transcripts, Zhang et al (2016) used DISRUPTION OF MEIOTIC CONTROL1 (DMC1); silencing of DMC1, or the presence of a truncated, dominant-negative DMC1 ( DN DMC1) causes pollen defects and male sterility. Thus, male sterility provides a readout for translocation of DN DMC1 mRNA fusions moving from the rootstock into a grafted, wild-type scion.…”
mentioning
confidence: 99%